Sistem Informasi Akreditasi UNMA Banten Berbasis Web menggunakan Metode Waterfall - Rifqi Rifaldi (Admin Situstika, 2022)
Improving the quality of higher education education is a complex problem that is always interesting to understand in order to find solutions to improve it. Currently, many higher education institutions are competing to provide the best quality education to their stakeholders in an effort to produce graduates who are ready to work with global competitiveness. Management of institutional accreditation at UNMA Banten has so far been carried out manually, that is, the documents that have been prepared are still in hard file form so that the process of reviewing form data is less effective and takes quite a long time, then synchronizing existing form data in the Academic Information System with the Quality Assurance Agency also inappropriate. Seeing the existing problems, UNMA Banten created a system that can overcome the problems faced so that it can improve UNMA in the accreditation preparation process. This system was built using a structured design consisting of Flow of Document (FOD), Flow of System (FOS), Context Diagram, Data Flow Diagram (DFD), Entity Relationship Diagram (ERD) and Normalization using the MySQL Database and Sublime Text Tools as The text editor was then implemented at UNMA Banten by producing input of Higher Education Identity Data, Study Program Data, LKPT Preparation Team Data, External Certification Data, External Financial Audit Data, Study Program Accreditation Data, Higher Education Collaboration Data, New Student Selection Data, Weight Data Course Credit, Higher Education Lecturer Adequacy Data, Lecturer Academic Position Data, Lecturer Certification Data, Non-Permanent Lecturer Data, Lecturer Workload Data, Lecturer Productivity Data, Lecturer Recognition Data, Student Achievement Index Data, Competency Certificate Data, Student Achievement Data, Student Study Length Data, as well as producing output in the form of a Higher Education Performance Report (LKPT). This makes it easier to monitor institutional quality quickly, precisely and accurately and can help the accreditation management process at UNMA Banten.